Noise induced hearing loss among grass trimming workers - Jaafar, Nabeel Ibraheem (2011)
Introduction: Grass trimming workers work every day in a noisy environment as they carry the grass trimming machine on their back, such daily exposure for many years may contribute to noise induced hearing loss. Objective: To assess the hearing status of the grass trimming workers in KB and the nearby areas and to determine the prevalence of noise induced hearing loss among them. Methodology: This was a descriptive cross sectional study.The source population were from grass trimming worker works under USM Health Campus, Majlis Perbandaran Kota Bharu (MPKB) , Majlis Daerah Pasir Puteh, Bachok, Ketereh and Tumpat. The data was collected at HUSM /ORL-HNS outpatient clinic to fill the Proforma , otoscopic examination and hearing tests. Hearing tests consist of pure tone audiometry, tympanogram and distortion product otoacoustic emission. Results: A total of 77 grass trimming workers participate in this study. All of them were male with age range from 20-53 years old with majority of them fall in age group of 40-50years old. Two of the subjects were excluded as they have history of working in noisy job before and for at least 10 years. None of them use any protecting hearing device. Duration of work of grass trimmers were in between 1 to 33 years. The daily work was 4-5 hours with time of rest in between we found that 62 out 75 grass (82.7%) trimming worker have noise induced hearing loss with characteristic notch at 6 kHz , 4 kHz and 3 kHz. The noise induced hearing loss occurred in workers exposed to noise as early as two years in this job. The intensity of the noise from the machine is in between 91.3 to 100.7dB in a fluctuant manner. The left ear was the predominant side that was affected by hearing loss .All of the subjects was having mild hearing loss. Conclusion: The study showed that grass trimming job have occupational hazards of noise induced hearing loss. It occurs with one to two years working without any hearing protection device .The dip at 6kHz is a significant early sign for noise exposure. We strongly recommend that all the workers use the hearing protection device while doing grass trimming.